Geospatial Technologies for Monitoring Carbon Sequestration and Assessing Nature Based Solution for Climate Change Mitigation - Qasim, Muhammad (2025)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies